Patriarki dalam Keluarga Muslim di Danau Toba: Kajian Nilai Kekeluargaan dalam Islam Berdasarkan Tafsir Al-Lubab Karya M. Quraish Shihab - Hasibuan, Riza Sakhbani (Yayasan Albahriah Jamiah Indonesia, 2025)
This study examines the patriarchal system in Muslim families in Lake Toba, North Sumatra, which is influenced by Batak patrilineal culture and Islamic teachings. As a minority community, Muslim families in this region face strong challenges from the Dalihan Na Tolu tradition that places men as the center of authority. Although Islam emphasizes gender justice and balance, patriarchal practices are still evident in decision-making, role distribution, inheritance rights, and women’s access to public spaces. The objectives of this study are to describe the forms of patriarchy in Muslim families in Lake Toba, analyze Islamic family values ​​based on Quraish Shihab’s Tafsir Al-Lubab, and uncover the potential for creating harmonious families through contextual interpretation of the Qur’an. This study uses a qualitative approach. Primary data were obtained through participant observation, in-depth interviews with eight Muslim families and a religious figure, and a study of Tafsir Al-Lubab as the main source. Secondary data came from academic literature, journals, and Dalihan Na Tolu customary rules. The analysis was conducted using the thematic interpretation method (mauḍūʻī) of QS. al-Nisāʻ [4]: ​​34, QS. al-Rūm [30]: 21, and QS. al-Nisāʻ [4]: ​​86 to see how Islam offers solutions to patriarchal practices. The results of the study show that patrilineal customs strengthen male dominance in family leadership, especially in aspects of inheritance and strategic decisions. However, a new dynamic emerges when women play a role in the economy, children’s education, and household decisions. Tafsir Al-Lubab emphasizes that qiwāmah is not domination, but rather a trust based on compassion and justice. The values ​​of mawaddah and raḥmah are the basis of a harmonious, equal, and gender-just family.